Biofunctionalization of bioactive ceramic scaffolds to increase the cell response for bone regeneration. (30th July 2021) - Zamuner, Annj; Brun, Paola; Ciccimarra, Roberta; Ravanetti, Francesca; Veschini, Lorenzo; Elsayed, Hamada; Sivolella, Stefano; Iucci, Giovanna; Porzionato, Andrea; Silvio, Lucy Di; Cacchioli, Antonio; Bernardo, Enrico; et al.
Abstract: Biofunctionalization was investigated for polymers and metals considering their scarce integration ability. On the contrary few studies dealt with ceramic biofunctionalization because the bioactive and bioresorbable surfaces of ceramics are able to positively interact with biological environment. In this study the cell-response improvement on biofunctionalized wollastonite and diopside-based scaffolds was demonstrated. The ceramics were first obtained by heat treatment of a silicone embedding reactive oxide fillers and then biofunctionalized with adhesive peptides mapped on vitronectin. The most promising in vitro results, in terms of h-osteoblast proliferation and bone-related gene expression, were reached anchoring selectively a peptide stable toward proteolytic degradation induced by serum-enriched medium. In in vivo assays the anchoring of this protease-stable adhesive peptide was combined with self-assembling peptides, for increasing cell viability and angiogenesis. The results demonstrated external and internal cell colonization of biofunctionalized scaffolds with formation of new blood vessels (neoangiogenesis) and stimulation of ectopic mineralization.